Pengaruh Profitabilitas dan Leverage Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Sektor Basic Materials yang Terdaftar di BEI Periode 2020 – 2024 - Cesar Diaz Pratama; G. A. Sri Oktaryani (Ikatan Da'i Indonesia, 2026)
This study aims to empirically analyze the effect of profitability and leverage on firm value with dividend policy as a moderating variable in manufacturing companies within the basic materials subsector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The population of this study consists of 108 companies, with a sample of 16 companies selected using purposive sampling, resulting in 80 observations. This research employs a quantitative approach using secondary data in the form of companies’ annual financial statements. Data analysis techniques include descriptive statistics, classical assumption tests, and hypothesis testing, which consist of Moderated Regression Analysis (MRA), t-test, F-test, and coefficient of determination (R² test). The results show that profitability has no significant effect on firm value, with a significance value of 0.9710 > 0.05. Leverage also has no significant effect on firm value, with a significance value of 0.1277 > 0.05. Dividend policy is able to moderate the effect of profitability on firm value, with a significance value of 0.0139 < 0.05. However, dividend policy is not able to moderate the effect of leverage on firm value, with a significance value of 0.3641 > 0.05.